A Robust Nonvolatile Resistive Memory Device Based on a Freestanding Ultrathin 2D Imine Polymer Film. Issue 28 (17th May 2019) - Liu, Jie; Yang, Fangxu; Cao, Lili; Li, Baili; Yuan, Kuo; Lei, Shengbin; Hu, Wenping
Abstract: Here, the synthesis of a wafer‐scale ultrathin 2D imine polymer (2DP) film with controllable thickness from simple benzene‐1, 3, 5‐tricarbaldehyde (BTA) and p ‐phenylenediamine (PDA) building blocks is reported using a Schiff base polycondensation reaction at the air–water interface. The synthesized freestanding 2DP films are porous, insulating, and more importantly, covalently linked, which is ideally suited for nonvolatile memristors that use a conductive filament mechanism. These devices exhibit excellent switching performance with high reliability and reproducibility, with on/off ratios in the range of 10 2 to 10 5 depending on the thickness of the film. In addition, the endurance and data retention capability of 2DP‐based nonvolatile resistive memristors are up to 200 cycles and 8 × 10 4 s under constant voltage stress at 0.1 V. The intrinsic flexibility of the covalent organic polymer enables the fabrication of a flexible memory device on a polyimide film, which exhibits as reliable memory performance as that on the rigid substrate. Moreover, the 2DP‐based memory device shows outstanding thermal stability and organic solvent resistance, which are desirable properties for applications in wearable devices. Abstract : Freestanding, porous, insulating, and covalently linked 2DP films, which are ideally suited for nonvolatile memristors, are synthesized at the air–water interface within wafer scale. Nonvolatile memristors based on these films exhibit excellent switching performance with high reliability and reproducibility, with on/off ratios in the range of 10 2 to 10 5 depending on the thickness of the film.